2022
DOI: 10.1088/2053-1591/ac7b72
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and fluorescence properties of MgAl2O4: Tb3+ nanorod-like phosphors

Abstract: A series of MgAl2O4: x% Tb3+ (x=1.0–6.0) phosphors was prepared by a hydrothermal-assisted light burning method. The crystal structure, morphology and fluorescence properties of the samples were investigated. The results indicated that when the the hydrothermal and light burning temperatures were determined to be 120 °C and 1100 °C, respectively, the crystallinity for Mg4Al2(OH)14 and NH4Al(OH)2CO3 biphasic precursors is the best, conducive to generating pure phase MgAl2O4 nanorod-like phosphors. The entry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…MgAl2O4:Eu 3+ and Dy 3+ phosphors were developed by solgel method and they were calcined for 5 h between 600 and 900 ºC [20]. Using a variety of techniques, doped MgAl2O4 phosphors containing Dy 3+ , Tb 3+ and Eu 3+ have also been synthesized [21][22][23][24]. Recent study has demonstrated that red emission of Eu-doped phosphors caused by 5 Do → 7 FJ transitions.…”
Section: Introductionmentioning
confidence: 99%
“…MgAl2O4:Eu 3+ and Dy 3+ phosphors were developed by solgel method and they were calcined for 5 h between 600 and 900 ºC [20]. Using a variety of techniques, doped MgAl2O4 phosphors containing Dy 3+ , Tb 3+ and Eu 3+ have also been synthesized [21][22][23][24]. Recent study has demonstrated that red emission of Eu-doped phosphors caused by 5 Do → 7 FJ transitions.…”
Section: Introductionmentioning
confidence: 99%